Introduction to clinical methods in communication disorders - Paul, Rhea; Simmons, Elizabeth Schoen (Baltimore, Maryland : Paul H. Brookes Publishing Co., 2021)
'With a new co-editor and several new contributors, this bestselling core textbook on communication disorders is better than ever in its fourth edition, thoroughly revised and based on updated ASHA standards'--
'Fully updated and revised based on the 2020 ASHA standards and recent AAA standards, the new edition of this bestseller is the core textbook for all students in clinical methods courses--and a reliable reference for practicing SLPs and audiologists. Covering a broad range of disorders and developmental levels, this text sets emerging professionals on the path toward mastering all the fundamentals of practice, from conducting effective assessment and intervention to ensuring that practices are family-centered and culturally inclusive.'--
Introduction to clinical practice in communication disorders / Rhea Paul -- Ethical practice in communication disorders / Barbara H. Jacobson and Arlene E. Carney -- Evidence-based decision making in communication assessment and intervention / Mary Beth Schmitt, Laura M. Justice, and Marc E. Fey -- Principles of communication assessment / Elizabeth Schoen Simmons -- Communication sampling procedures / Rhea Paul, Nan Bernstein Ratner, Marta Korytkowska, and Ciara Leydon -- Communication intervention: principles and procedures / Lizbeth H. Finestack and Jessica A. Brown -- Professional communication: effective counseling techniques and clinical documentation strategies / David Andrews -- Public policies affecting clinical practice / Charles H. Carlin and Marie C. Ireland -- Clinical service delivery and work settings / Jamie Marotto, Ellen Massucci, Cristina M. Pino, and Taryn M. Rogers -- Issues of cultural and linguistic diversity / Aquiles Iglesias, Raúl Rojas, and Brian A. Goldstein -- Technology and communication disorders / Elizabeth Schoen Simmons and Brandon Eddy -- Family-centered practice / Patricia A. Prelock and Ashley R. Brien -- Principles of clinical observation / Nancy E. Hall
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on November 05, 2020).
Added to collection customer.56279.3
Keywords: Speech therapy; Audiology; Communication Disorders -- therapy; Clinical Medicine -- methods; Speech-Language Pathology -- methods; Speech Therapy; Audiology; Orthophonie; Audiologie; Audiology; Speech therapy